2014
DOI: 10.1089/acu.2013.1002
|View full text |Cite
|
Sign up to set email alerts
|

Positioning Standardized Acupuncture Points on the Whole Body Based on X-Ray Computed Tomography Images

Abstract: The goal of this research was to position all the standardized 361 acupuncture points on the entire human body based on a 3-dimensional (3D) virtual body. Digital data from a healthy Korean male with a normal body shape were obtained in the form of cross-sectional images generated by X-ray computed tomography (CT), and the 3D models for the bones and the skin's surface were created through the image-processing steps. The reference points or the landmarks were positioned based on the standard descriptions of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…We found that the 37% of the 361 standardized acupoints on the entire body were automatically linked to the reference points. The reference points accounted for 11% of the 361 acupoints, and the remaining acupoints (52%) were positioned point-by-point by using 3D computer graphics libraries [ 16 ]. In this study, we increased the number of subjects to six and confined the positioning area to their heads.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We found that the 37% of the 361 standardized acupoints on the entire body were automatically linked to the reference points. The reference points accounted for 11% of the 361 acupoints, and the remaining acupoints (52%) were positioned point-by-point by using 3D computer graphics libraries [ 16 ]. In this study, we increased the number of subjects to six and confined the positioning area to their heads.…”
Section: Discussionmentioning
confidence: 99%
“…The procedure for reconstructing the surfaces of the skin and the skull from the stack of 2D images of the six individual is basically the same as that used in [ 16 ] for a single person with a normal body shape. In brief, first, the DICOM images are converted to 8-bit BMP format because of memory issues.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that the acupoints are defined in a 3D space, a 3D face model is useful for acupoint localization. The 3D Morphable Models (3DMM) [8,9,10,11] are common for face analysis because the intrinsic properties of 3D faces provide a representation that is immune to intra-personal variations. Given a single facial input image, a 3DMM can recover 3D face via a fitting process.…”
Section: Acupuncture Point Localizationmentioning
confidence: 99%
“…Recent articles support a relationship between acupuncture points/meridians and fascia [1]. Specifically, anatomical observations of body scan data demonstrated that the fascia network resembles the theoretical meridian system in salient ways, and physiological, histological, and clinical observations support this hypothesis [11, 12].…”
Section: Introductionmentioning
confidence: 99%